Projecto e Construção de Linha Aérea Alta Tensão - Alice Araújo da Silva (2019)
The execution of the dissertation project "Project and Construction of High Voltage Overhead Line" took place during the graduate traineeship at EDP - Distribuição SA, in the Department of Services for Networks, in the Department of Investment Management.The proposal is based on the elaboration of a project of a high voltage line of 60 KV, which connects the substation of Nogueira da Regedoura, in Santa Maria da Feira, District of Aveiro, Espinho, in the same district. It is a double line consisting of six ACSR 325 conductor cables and a guard cable OPGW AA/ACS/ST 157/60 24 FO, about 3.2 km long and has a transport capacity of 120 MW.The project was drafted according the guidelines of Portugal's High Voltage Power Line Safety Regulation, complying with all the provisions on the location of the supports, minimum distances required, for their structures and their surroundings, as well as, for the conductors of the line.The experience and sensitivity of the designer are determining factors when carrying out a project. The maximum traction of the conductor or guard cable is one of these characteristics. The determination of the maximum voltage to be used was calculated not only by Portugal's High Voltage Power Line Safety Regulation and the maximum safety traction of the condutctor, but also considered the traction, on average, to which the conductor will be subjected daily (EDS), trying not to exceed the fatigue of the conductor under dynamic regime.It was the object of work to automate the systematic calculation of the stability check of the supports, being only necessary the characterization of the span and its angle, the maximum traction and the type of support. The dissertation work was performed with the Microsoft Office Excel software.